2012
DOI: 10.1371/journal.pone.0033610
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification, Phylogenetic Status, and Geographic Distribution of Culicoides oxystoma (Diptera: Ceratopogonidae) in Israel

Abstract: Culicoides oxystoma (Diptera: Ceratopogonidae) is an important vector species, reported mainly from Asia, with high potential to transmit viral diseases affecting livestock. In Japan, many arboviruses have been isolated from C. oxystoma, suggesting it as a key player in the epidemiology of several Culicoides-borne diseases. Over the years, C. oxystoma has also been reported in the Middle East region, including Israel. In this region, however, C. oxystoma cannot be easily distinguished morphologically from its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 33 publications
5
41
0
Order By: Relevance
“…There has been a great deal of confusion in the literature between this species, C. schultzei and C. subschultzei [8], [25], [37]. Boorman (1989) suggested that most of the records of C .…”
Section: Discussionmentioning
confidence: 99%
“…There has been a great deal of confusion in the literature between this species, C. schultzei and C. subschultzei [8], [25], [37]. Boorman (1989) suggested that most of the records of C .…”
Section: Discussionmentioning
confidence: 99%
“…Initial identification of the dominant species, C. imicola and members of the Culicoides schultzei species group (difficult to separate morphologically), was initially based on the wing spot pattern and other diagnostic morphological traits (www.culicoides.net). In parallel, molecular identification of individual midges was carried out by internal transcribed spacer 1 (ITS-1) ribosomal DNA (rDNA) PCR, as previously described (29). The midges were further morphologically categorized according to their parity (oviposition) status, which in this genus varies with abdominal pigmentation (30).…”
Section: Methodsmentioning
confidence: 99%
“…It may be that C. oxystoma and C. kingi also contribute to the transmission of the AHSV in Senegal, and more broadly in West Africa (Fall et al, 2015). Culicoides oxystoma has been reported as a putative vector for BTV in northern India (Prasad et al, 1999), as involved in the transmission of bovine arboviruses such as Akabane virus in Japan (Kurogi et al, 1987;Yanase et al, 2005) and is suspected of transmitting the epizootic haemorrhagic disease virus (EHDV) in Israel (Morag et al, 2012).…”
Section: Introductionmentioning
confidence: 99%